Software educativo para mejorar el proceso enseñanza-aprendizaje de la asignatura de estudios sociales del bloque 1,2,3 para el noveno año de educación general básica del colegio nocturno Doctor Benjamín Carrión de la ciudad de Loja, periodo lectivo 2012-2013 - Burneo Nieto, Gabriela Judith (2013)
Education in Ecuador since its inception was organized to educate all people equally regardless of social or economic class, so as members of this society and professional future I decided to make this thesis with the name of the Educational Software Social Studies subject blocks 1, 2 and 3, will improve the teaching-learning process of the students of the Ninth Year of Basic General Education Evening College "Doctor Benjamin Carrion" in the city of Loja, 2012-2013 period, my illusion has led me to develop this project because in that school has no educational multimedia tool to improve teaching and learning process, and thus obtain a Bachelor of Science in Education specializing in Educational Computing National University Loja. To comply with the general objective is development and implementation of educational software for students in the Ninth Year of the subject of social studies methods such as inductive - deductive, scientific, descriptive, also for the collection of information techniques used as a survey of students and an interview with the teachers who teach the subject of Social Studies, then performed the analysis and interpretation of data, responding to the variables found as educational software and teaching processes learning. For the construction and development of educational software tool was used Swish Max and with the help of other programs with which we proceeded to the editing of sounds, images and videos for optimal development, for further reference also included a user manual and will serve as a programmer to help with software development.